ARITMATIKA: An innovative application to enhance higher order thinking skills in students through problem-based learning - Utami, Anita Dewi; Suwarman, Ramdhan Fazrianto; Cahyowati, Ety Tejo Dwi; Rofiki, Imam; Ningseh, Sinta Agustin (Jurnal Kajian Pembelajaran Matematika, 2024)
The objective of this research is to develop "ARITMATIKA," an innovative application designed to support students' Higher Order Thinking Skills (HOTS) through Problem-Based Learning. The research methodology employed is based on the general Plomp educational problem-solving model, encompassing three of its five phases: the initial investigation phase, the design phase, and the realization phase. This use of three out of the five phases is due to the preliminary nature of this research. The findings indicate that ARITMATIKA is suitable for use in enhancing learning outcomes in the Introduction to Geometry course.